Swansea Bay tidal lagoon annual energy estimation. (1st January 2016) - Petley, Sean; Aggidis, George
Abstract: UK Energy policy is focused on the challenges posed by energy security and climate change, however, efforts to develop a low-carbon economy have overlooked tidal energy a vast and unexploited worldwide resource. Since 1981, UK tidal lagoon schemes have been recommended as an economically and environmentally attractive alternative to tidal barrages. More recently, two proposals for tidal lagoons in Swansea Bay have emerged and there have been several reports documenting the potential to harness significant tidal energy from Swansea Bay using a tidal lagoon. This paper assists in determining a realistic approximation of the energy generation potential in Swansea Bay, a numerical estimation is obtained from a zero dimension, 0D, 'backwards difference' computational model, utilising the latest turbine data available and high-resolution bathymetric data. This paper models the behaviour of the tidal lagoon in dual mode generation, in line with the above proposals. The results of model testing using a variety of fixed and variable parameters are displayed. The ebb mode model with provision for pumping at high tide is then explored further by carrying out optimisations of the starting head, number of turbines and turbine diameter in order to determine the maximum annual energy output from the tidal lagoon. Highlights: OD modelling of Swansea Bay tidal lagoon for dual and ebb mode generation. Hydro turbine models with provision for sixteen 7 m diameter turbines. SeaZone bathymetric data manipulated using ArcGIS mapping. Dual mode approx. 480 GW h per annum & ebb mode increases annual energy gen. by 24%. Lagoon optimized ebb mode could improve generation by 50% compared to dual mode.